2009
DOI: 10.1186/1756-3305-2-60
|View full text |Cite
|
Sign up to set email alerts
|

A zoonotic focus of cutaneous leishmaniasis in Addis Ababa, Ethiopia

Abstract: BackgroundCutaneous leishmaniasis (CL) is endemic in the highlands of Ethiopia, and almost always caused by Leishmania aethiopica. Hitherto, Addis Ababa (the capital city of Ethiopia) was not considered endemic for CL, mainly due to absence of epidemiological and field ecological studies. This report summarizes the preliminary epidemiological investigation that proved the existence of active transmission in southeastern Addis Ababa.ResultsActive case finding surveys were conducted in 3 localities, Saris, Kalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
65
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 18 publications
10
65
1
Order By: Relevance
“…The human cases of CL, sand fly vectors and reservoir hyrax species responsible for L. aethiopica transmission are known to commonly occur at altitudes similar to our prediction: the previously characterised CL foci in Ethiopia lie between 1,400 and 2,700 m above MSL (Ashford et al, 1973;Ashford, 1977;Negera et al, 2008;Lemma et al, 2009). Considering geographical and individual variables, Morrone et al (2011) documented clustering of CL cases in males living at altitudes above 2,000 m above MSL in the Tigray regional state.…”
Section: Discussionmentioning
confidence: 75%
“…The human cases of CL, sand fly vectors and reservoir hyrax species responsible for L. aethiopica transmission are known to commonly occur at altitudes similar to our prediction: the previously characterised CL foci in Ethiopia lie between 1,400 and 2,700 m above MSL (Ashford et al, 1973;Ashford, 1977;Negera et al, 2008;Lemma et al, 2009). Considering geographical and individual variables, Morrone et al (2011) documented clustering of CL cases in males living at altitudes above 2,000 m above MSL in the Tigray regional state.…”
Section: Discussionmentioning
confidence: 75%
“…Our patients all came from the Ethiopian highlands around Mekelle. It has been demonstrated that CL on the Ethiopian highlands (> 2,000 meters) is caused by L. aethiopica, which was the only species isolated from patients living in the highlands of different regions including Tigray in several studies [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Here we report the presence of LR in Ethiopia, where L. aethiopica is to date still the only species found in the highlands causing CL [16][17][18][19][20], and describe the mucosal involvement in this uncommon clinical variant.…”
Section: Introductionmentioning
confidence: 99%
“…For species like bush hyrax, which has a relatively long (24-30 weeks) gestation period (Barry and Hoeck, 2013) and reproduction synchronized with seasonal rainfall (Barry and Mundy, 1998), the loss of five adult individuals in just one season, raises a worrisome sustainability concern. Note that bush hyraxes are susceptible to viral pneumonia and tuberculosis (Sale, 1966), they harbour Leishmania (Lemma et al, 2009), nematode and different arthropod ectoparasites (Barry and Shoshani, 2000). Even though we did not investigate this topic, the small hyrax population might have suffered genetic stochasticity that could be explained by compromised resistance to diseases and parasites, as some of the adult individuals looked unusually weak during the dry season a few days before the population count dropped.…”
Section: Conservation Concernmentioning
confidence: 99%
“…Studies on population status and diet are also scarce. From a human health point of view, several reports explained the reservoir role of hyraxes in the epidemiology of cutaneous leishmaniasis, a form of Old World leishmaniasis occurring in the highlands of Kenya and Ethiopia (Ashford et al, 1973;Lemma et al, 2009). …”
Section: Introductionmentioning
confidence: 99%